2022
DOI: 10.3389/fpls.2022.927229
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen optimization coupled with alternate wetting and drying practice enhances rhizospheric nitrifier and denitrifier abundance and rice productivity

Abstract: Optimizing nitrogen (N) fertilization without sacrificing grain yield is a major concern of rice production system because most of the applied N has been depleted from the soil and creating environmental consequences. Hence, limited information is available about nutrient management (NM) performance at a specific site under alternate wetting and drying (AWD) irrigation compared to conventional permanent flooding (PF). We aimed to inquire about the performance of NM practices compared to the farmer’s fertilizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…With respect to CF, the adoption of AWD cycles after tillering was shown to result in a lower plant growth during the early vegetative stages, particularly for root development, in line with previous findings (Suriyagoda et al 2014;Weerarathne et al 2015;Zhou et al 2020;Wu et al 2022). Several authors have however observed a positive plant growth response under AWD, with an increase in root length and dry matter accumulation (Kato and Okami 2010;Thakur et al 2011;Hazra and Chandra 2016;Abid et al 2022). It is well-known that rice plants grown under AWD can regulate the growth of above and belowground biomass in different proportions depending on the stage of the growing cycle (Zhang et al 2021).…”
Section: Influence Of Water Management On N Availability and Plant Up...mentioning
confidence: 99%
“…With respect to CF, the adoption of AWD cycles after tillering was shown to result in a lower plant growth during the early vegetative stages, particularly for root development, in line with previous findings (Suriyagoda et al 2014;Weerarathne et al 2015;Zhou et al 2020;Wu et al 2022). Several authors have however observed a positive plant growth response under AWD, with an increase in root length and dry matter accumulation (Kato and Okami 2010;Thakur et al 2011;Hazra and Chandra 2016;Abid et al 2022). It is well-known that rice plants grown under AWD can regulate the growth of above and belowground biomass in different proportions depending on the stage of the growing cycle (Zhang et al 2021).…”
Section: Influence Of Water Management On N Availability and Plant Up...mentioning
confidence: 99%
“…Previous research shows that slow-release fertilizers, water-soluble fertilizers, crop straw, and other organic fertilizers are common fertilizer sources to replace chemical fertilizers in crop production, improving the quality of cultivated land while ensuring the quality of agricultural products and the safety of the ecological environment. Abid et al reported that 40% chemical N replaced by pig manure promoted higher rice production, followed in descending order by 40% chemical N replaced by organic slow-release farmer fertilizer practices [20]. In both organic (farmyard manure, cow dung, biogas slurry, sugarcane bagasse) and inorganic (gypsum and lignite) amendments, cow dung significantly improved rice growth and physiological parameters [21].…”
Section: Introductionmentioning
confidence: 99%